Predictive value of ventilatory inflection points determined under field conditions. Issue 9 (2nd May 2016) - Heyde, Christian; Mahler, Hubert; Roecker, Kai; Gollhofer, Albert
ABSTRACT: The aim of this study was to evaluate the predictive potential provided by two ventilatory inflection points (VIP1 and VIP2 ) examined in field without using gas analysis systems and uncomfortable facemasks. A calibrated respiratory inductance plethysmograph (RIP) and a computerised routine were utilised, respectively, to derive ventilation and to detect VIP1 and VIP2 during a standardised field ramp test on a 400 m running track on 81 participants. In addition, average running speed of a competitive 1000 m run ( S 1 k ) was observed as criterion. The predictive value of running speed at VIP1 ( S VIP1 ) and the speed range between VIP1 and VIP2 in relation to VIP2 (VIPSPAN ) was analysed via regression analysis. VIPSPAN rather than running speed at VIP2 ( S VIP2 ) was operationalised as a predictor to consider the covariance between S VIP1 and S VIP2 . S VIP1 and VIPSPAN, respectively, provided 58.9% and 22.9% of explained variance in regard to S 1 k . Considering covariance, the timing of two ventilatory inflection points provides predictive value in regard to a competitive 1000 m run. This is the first study to apply computerised detection of ventilatory inflection points in a field setting independent on measurements of the respiratory gas exchange and without using any facemasks.